Long‐term therapeutic effect in nonhuman primate eye from a single injection of anti‐VEGF controlled release hydrogel. Issue 2 (10th June 2019) - Yu, Yu; Lin, Xingyan; Wang, Qilin; He, Mingguang; Chau, Ying
Abstract: Wet age‐related macular degeneration (wet‐AMD) is a leading cause of irreversible blindness. Current treatment of AMD requires monthly intravitreal injection, which is difficult to be implemented in many parts of the world. In recent years, controlled release of anti‐vascular endothelial growth factor (VEGF) therapeutics has attracted intense research interest aiming to reduce the injection frequency to one or two times per year. In this study, we evaluated the in vivo pharmacokinetics and the long‐term therapeutic efficacy of an in situ hydrogel encapsulating an anti‐VEGF antibody in nonhuman primates. We show that after a single injection of anti‐VEGF controlled release hydrogel, a relatively constant concentration of drug can be maintained in the monkey eye for at least 5 months and the dose was sufficient for the treatment of recurrent choroidal neovascularization induced by repeat laser photocoagulation in monkeys. Our result suggested that when formulated into a controlled release formulation, a single dose of anti‐VEGF may be sufficient for a half‐year treatment and controlled release may be a suitable strategy to reduce the injection frequency in the treatment of AMD in human.